2018
DOI: 10.1080/0167482x.2018.1476486
|View full text |Cite
|
Sign up to set email alerts
|

What makes a chronic pelvic pain patient satisfied?

Abstract: The data suggest that a focus on empathic communication may make a meaningful difference in meeting the needs of women with CPP as well as strengthening the provider/patient relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…Women who felt validated were generally more satisfied with treatment, even if their symptoms had not entirely resolved. This is a key message for treating physicians, and consistent with a prior qualitative survey of 90 patients with chronic pelvic pain: patient satisfaction was closely related to having healthcare providers who were compassionate and listened; pain relief was seldom mentioned as a source of patient satisfaction 36 . Many women in our study were at least somewhat satisfied with treatment, with several commenting their pain was successfully managed and that a positive relationship with a ‘good’ provider made the difference.…”
Section: Discussionsupporting
confidence: 85%
“…Women who felt validated were generally more satisfied with treatment, even if their symptoms had not entirely resolved. This is a key message for treating physicians, and consistent with a prior qualitative survey of 90 patients with chronic pelvic pain: patient satisfaction was closely related to having healthcare providers who were compassionate and listened; pain relief was seldom mentioned as a source of patient satisfaction 36 . Many women in our study were at least somewhat satisfied with treatment, with several commenting their pain was successfully managed and that a positive relationship with a ‘good’ provider made the difference.…”
Section: Discussionsupporting
confidence: 85%
“…Rowe et al found three domains of endometriosis care that could influence patient satisfaction with endometriosis care: (i) information that meets patients’ needs; (ii) being heard with empathy and respect; and (iii) technical competence. Similar domains were also found by two previous questionnaire studies investigating patient satisfaction ( Lukas et al , 2018 ; Wygant et al , 2019 ).…”
Section: Introductionsupporting
confidence: 87%
“…IC patients usually present with variable combinations of signs and symptoms resulting from underlying risk factors described previously, which are identified from the signalment and a careful history. Skepticism from medical providers can diminish patient satisfaction and outlook ( 197 , 198 ), and a qualitative study reported that women with IC commonly experience disbelief and pain dismissal from healthcare providers, which can prevent effective communication with them and lead to suboptimal care ( 199 ).…”
Section: Discussionmentioning
confidence: 99%